2009
DOI: 10.1097/ijg.0b013e31818456b9
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits, Depression, and Objectively Measured Adherence to Once-daily Prostaglandin Analog Medication in Glaucoma

Abstract: Objectively measured adherence to once-daily prostaglandin analog medication was good, and not influenced by treatment characteristics or patient factors including mild-to-moderate depression. The elevated social desirability suggests that self-reported adherence is not a reliable measure of adherence in glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…Self-report instruments per se have their limitations, such as respondent bias and errors in the recall of behavior [48]. In addition, in research designs using simple direct questions about medication that has possibly been forgotten, there is the potential for activating what the interviewee sees as socially desirable answer behavior [49,50]. More sophisticated NA self-report questionnaires use indirect, nonaccusatory questioning techniques to minimize the tendency to give socially desired answers.…”
Section: Introductionmentioning
confidence: 99%
“…Self-report instruments per se have their limitations, such as respondent bias and errors in the recall of behavior [48]. In addition, in research designs using simple direct questions about medication that has possibly been forgotten, there is the potential for activating what the interviewee sees as socially desirable answer behavior [49,50]. More sophisticated NA self-report questionnaires use indirect, nonaccusatory questioning techniques to minimize the tendency to give socially desired answers.…”
Section: Introductionmentioning
confidence: 99%
“…The second limitation is that self-reporting has inherent weaknesses, the main one being a tendency of a patient to give favourable answers to please the physician. Hollo et al [23] measured the influence of psychological characteristics on compliance with glaucoma medication. They found that social desirability was significantly increased in a cohort of glaucoma patients as compared with normal subjects.…”
Section: Limitationsmentioning
confidence: 99%
“…Intraocular pressure (IOP)-lowering medication eye drops are typically prescribed for life-long use to slow the progression of the disease; however, the effectiveness of this treatment heavily depends on patient adherence to the regimen. 24 There are numerous barriers to glaucoma treatment adherence noted in the literature, including medication side effects, eye drop administration, literacy levels, and the complexity of medication regimens. 3, 5–8 …”
mentioning
confidence: 99%